INJURIES OF THE KNEE LIGAMENTS - KINETOTHERAPY RECOVERY PROGRAMS - Francisc Tadeus Danelciuc (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The knee is the biggest joint of our body. Through its position and role in the static and dynamic biomechanics of lower limb and through its thin covering with mild tissues, the knee is one of the most liable joint prone to injuries and some pathological conditions. The knee also suffers in the case of immobilizations post traumas. From all traumas of the knees, ligaments lesions are more and more frequently. Those are produced as a result of the overuse through excessive forces, which causes tears of fibers. We distinguish three grades of ligaments lesions: a) lesions of 1st grade through stretching, without tears, b) lesions of 2nd degree - partial tears, c) complete lesions of 3rd grade. The goals in recovery programs of post-traumatic knee are: 1. To lower the pain; II. To stabilize the joint III. To reestablish joint ROM(Range of Motion), IV. Coordination of lower limb . Recovery of posttraumatic knee can be total if treatment and kinetics programs are well selected and right applied. Exceptions are done by old people whom osteoporosis and osteosclerosis processes can appear.